2010
DOI: 10.1159/000264620
|View full text |Cite
|
Sign up to set email alerts
|

Application of DC Beads in Hepatocellular Carcinoma: Clinical and Radiological Results of a Drug Delivery Device for Transcatheter Superselective Arterial Embolization

Abstract: Aim: Application of a drug delivery device for transarterial chem-oembolization (TACE) in patients with hepatocellular carcinoma (HCC). Clinical and radiological treatment assessment. Patients and Methods: 24 patients with liver cirrhosis and uni- or multifocal HCC underwent TACE with doxorubicin beads (DC BeadTM). The underly-ing cause of liver cirrhosis was hepatitis (A: n = 7; B: n = 10) or alco-hol consumption (n = 7). Patients presented with Child Pugh stage A (n = 15) and B (n = 9). The mean i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…Although one always considers optimistic resultsofreportedphaseIItrialswithadegreeofcaution,both ofthesestudiesreported12monthsurvivalinexcessof90% and2yearsurvivalwellabove80% [7,8].Thepresentstudy by Sadick and colleagues [1], although retrospective in its analysisandonasimilarlysmallpatientpopulation,reinforces the outcome data of the earlier reports, while treatment relatedadverseeventsremainrelativelyfew.Interestingly,8of 14patientswhosubsequentlydiedfollowingDCbeadTACE, succumbedbecauseofcirrhosisrelatedhepaticfailure,while theirtumoursremainedstable.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Although one always considers optimistic resultsofreportedphaseIItrialswithadegreeofcaution,both ofthesestudiesreported12monthsurvivalinexcessof90% and2yearsurvivalwellabove80% [7,8].Thepresentstudy by Sadick and colleagues [1], although retrospective in its analysisandonasimilarlysmallpatientpopulation,reinforces the outcome data of the earlier reports, while treatment relatedadverseeventsremainrelativelyfew.Interestingly,8of 14patientswhosubsequentlydiedfollowingDCbeadTACE, succumbedbecauseofcirrhosisrelatedhepaticfailure,while theirtumoursremainedstable.…”
supporting
confidence: 74%
“…However, these early results are both interestingandpromisinganddoneedtobefollowedup.Currentlyanumberoftrialproposalsareunderdiscussion.Thisis probablymostsignificantforpatientswhosediseaseisbeyond resectionortransplantation,inwhomweshouldseektoexaminethepossiblecombinationofDCbeadTACEwithsystemic sorafenib. The second group of patients who may very well benefitfromthistreatmentstrategyarethoseonthewaiting listfororthotopiclivertransplantation,whereDCbeadTACE mayofferaprolongationofthebridgetotransplantationwhile ThearticlebySadickandcolleagues [1]onTACEusingdoxorubicin (DC) beads for hepatocellular carcinoma (HCC) in this issue of OnkOlOgie is timely. HCC is a major global healthcare problem and is increasing in incidence.…”
mentioning
confidence: 99%
“…Two other trials reported higher rates of tumor response and longer time to progression for the loaded DC Bead as compared to a bland embolic microsphere with similar characteristics [27, 28]. As a result of these investigations, DEBDOX has been increasingly used as the first-line transcatheter treatment for HCC [2932]. …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it was reported in 1.8-3.7% of patients across treatments, and found to correlate with the extent of embolization; therefore, it was considered to be the result of inadvertent embolization (26,29). Post-procedural transient elevation of liver enzymes has also been reported in many TACE studies (27,29). In our research, although there was a statistically significant elevation of liver enzymes 3 days postembolization, there were no statistically significant differences between baseline and 1 month after the procedure.…”
Section: Discussionmentioning
confidence: 99%